Macroeconomics - Mankiw, N. Gregory (New York, 2008)
Mankiw's Macroeconomics is popular, widely adopted and well known for clearly communicating the principles of Macroeconomics in a concise and accessible way. The sixth edition maintains the core features that have made a bestselling Macroeconomics text - a balance of coverage between short and long-run issues, an integration of Keynesian and classical ideas, a variety of simple models and the incorporation of real world issues and data through case studies and FYI boxes. An outstanding package of support materials, includes the student web-support site 'Macrobytes'. The sixth edition includes new coverage of the decline in working hours in Europe, more extensive discussion of business-cycle facts to introduce the subject of short-run economic fluctuations and new case studies and FYI boxes.
Keywords: Macroeconomics